Understanding Franz Kafka from the Neuroscientific Perspective - Mushiake, Hajime (Brain and nerve, 2024)
Franz Kafka (1883-1924) was a novelist from what is now the Czech Republic, and is one of the figures who symbolize modern world literature. Although his works are more than 100 years old, Kafka displays amazing foresight regarding modern society; his writing portrays many original and unusual settings with extremely realistic expressions of individuals who find themselves in solitude caught in a huge inhuman system that typifies the current society. In this report, I discuss the association between such originality and Kafka's solitary interiority from a neuroscientific perspective.
Keywords: významné osobnosti; Neurosciences; dějiny 19. století; Humans; Literature, Modern; Czech Republic; novodobá literatura; neurovědy; Famous Persons; History, 20th Century; dějiny 20. století; lidé; History, 19th Century; Česká republika